2016
DOI: 10.1177/1465116516631142
|View full text |Cite
|
Sign up to set email alerts
|

Loving it but not feeling it yet? The state of European identity after the eastern enlargement

Abstract: The inclusion of 11 new member states from the former Eastern bloc constitutes a significant challenge to the European Union in various respects. Many worry that whatever tenuous ‘European identity’ existed prior to the eastern enlargement, it has now become so diluted that no meaningful European political community can form. We provide an empirical account of the state of European identity after the eastern enlargement through a comparative analysis of affective and cognitive European identity in the old and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Bringing European integration into the equation may help solving this puzzle as the youngest cohorts might identify more as European than their older counterparts. Indeed, it has been demonstrated that citizens' European identification and support for European integration are related to their generation (Ceka and Sojka 2016;Down and Wilson 2013). Moreover, we observe in our data that younger cohorts tend to identify more often primarily with an 'other' community, which includes Europe, but also the municipality and province.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Bringing European integration into the equation may help solving this puzzle as the youngest cohorts might identify more as European than their older counterparts. Indeed, it has been demonstrated that citizens' European identification and support for European integration are related to their generation (Ceka and Sojka 2016;Down and Wilson 2013). Moreover, we observe in our data that younger cohorts tend to identify more often primarily with an 'other' community, which includes Europe, but also the municipality and province.…”
Section: Discussionsupporting
confidence: 50%
“…The impact of regionalization on identification is, however, expected to be stronger when regionalization takes place at a young age. Similar to other political attitudes, it has been observed in the context of the development of European identification that people who came of age when their country was part of the EU tend to identify more strongly with the EU than people who were already deep into adulthood (Ceka and Sojka 2016).…”
Section: Theorizing Feedback Effects Of Experiences Of Institutional mentioning
confidence: 53%
“…The inclusion of the year of accession of the country of residence to the EU is justified by the fact that the length of membership plays a role in shaping citizens' affection and perception of Europe (Sanders, Bellucci, Tóka, & Torcal, ). In a similar vein, since the literature pointed out differences in the identification with Europe between western and eastern Member States (Ceka & Sojka, ), Equation is estimated for the whole sample but also separately for the two groups of countries.…”
Section: Cohesion Policy Implementation Trust In the Eu And Europeanmentioning
confidence: 99%
“…We move from the well-established idea that individuals hold multiple (Kohli, 2000: 116), nested (Díez Medrano and Gutiérrez, 2001), and partially overlapping (Risse, 2005: 296; see also Aksoy and Hadzic, 2019) identities. We recognise that these identities have both a civic and a cultural component (Bruter, 2003) and that individuals experience their identities in different spheres, insofar as their belonging to the group is grounded both in cognitive and affective processes (Ceka and Sojka, 2016). Thus, strong national identities do not necessarily have to be detrimental to European integration as long as they maintain an element of inclusiveness.…”
Section: The Euro As Identity Ma(r)kermentioning
confidence: 99%